KEHIDUPAN BERAGAMA RAJA KERTANAGARA - Hariani Santiko (KALPATARU, 2020)
During the reign of King Kertanagara the last ruler of Singasari, the Buddhist Tantrayana and the Siwa Bhairawa merging together into one religious system. The motivation behind the merging of the two religions is not clear, it may have been tolerant nature of the king or to strengthen the kingdom to face the Chinese enemy Kubilai Khan. For this reason, king Kertanagara built two Siva-Buddhist temples, Candi Jawi and Candi Singasari. Pada masa pemerintahan Raja Kertanagara, penguasa terakhir Singasari, Buddha Tantrayana dan Siwa Bhairawa bergabung menjadi satu sistem agama. Motif di balik penggabungan kedua agama tersebut belum jelas. Mungkin karena sifat toleran Raja atau untuk memperkuat kerajaan dalam menghadapi musuh dari Cina, Kubilai Khan. Dengan alasan tersebut, Raja Kertanagara membangun dua kuil Siwa-Buddha, Candi Jawi dan Candi Singasari.